Effect of Probiotic Thepax® and Saccharomyces cerevisiae Supplementation on Performance and Egg Quality of Laying Hens - Yousefi, M.; Karkoodi, K. (International Journal of Poultry Science, 2006)
An experiment was conducted to evaluate the effects of different levels of probiotic Thepax® (0.05, 0.1 and 0.15 %) and yeast (Saccharomyces cerevisiae) (0.05, 0.1 and 0.15 %) on performance and egg quality of laying hens. Two hundred and ten 63 wk of age Hy-line W-36 hens were used. The birds were assigned seven treatment groups in a randomized complete block design, with three replicates each with ten hens. The hens performance and egg parameters were evaluated on the three 28-d periods. The results of body weight changes, feed intake, feed conversion ratio, egg production, egg weight, shell percent and albumin weight did not indicate any treatment effect (P>0.05). Shell weight, shell thickness, yolk weight and yolk cholesterol were significantly (P=0.05) different among treatment groups. Yolk cholesterol was lower for 3, 5, 6 and 7th treatments compared to the control. The use of probiotic and Saccharomyces cerevisiae were not affected by production. But, egg quality did improved from 63 to 75 weeks of age.